A comparative study of glycerol dehydration catalyzed by micro/mesoporous MFI zeolites - Possato, Luiz Gustavo [UNESP]; Diniz, Rosiane N. [UNESP]; Garetto, Teresita; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Martins, Leandro [UNESP] (Elsevier, 2013)
The catalytic properties of monomodal microporous and bimodal micro-mesoporous zeolites were investigated in the gas-phase dehydration of glycerol. The desilication methodology used to produce the mesoporous zeolites minimized diffusion limitations and increased glycerol conversion in the catalytic reaction due to the hierarchical system of secondary pores created in the zeolite crystals. The chemical and structural properties of the catalyst were studied by X-ray diffraction, nitrogen adsorption-desorption isotherms, NH3-TPD and pyridine chemisorption followed by IR-spectroscopy. Although the aim was to desilicate to create mesoporosity in the zeolite crystals, the desilication promoted the formation of extra-framework aluminum species that affected the conversion of glycerol and the products distribution. The results clearly show that the mesoporous zeolites with designed mesopore structure allowed a rapid diffusion and consequently improved the reaction kinetics. However, especial attention must be given to the desilication procedure because the severity of the treatment negatively interfered on the Brønsted and Lewis acid sites relative concentration and, consequently, in the efficiency of the catalysis performed by these materials. On the other hand, during the catalytic reaction, the intracrystalline mesopores allowed carbonaceous compounds to be deposited herein, resulting in less blocked micropores and catalysts with higher long-term stability.
Keywords: Acrolein; Deactivation; Glycerol dehydration; Mesoporous materials; Zeolites; Carbonaceous compounds; Extra-framework aluminum species; Glycerol dehydrations; Nitrogen adsorption-desorption; Products distributions; Relative concentration; Catalysis; Catalysts; Dehydration; Hierarchical systems; Microporosity; Reaction kinetics; X ray diffraction; Glycerol